Interlayer Triplet–Triplet Energy Transfer in Nanosized Molecular Layers - Ibrayev, N.Kh.; Aimukhanov, A.K.; Seliverstova, E.V. (Springer, 2009)
The results of the study of interlayer triplet-triplet energy transfer from anthracene molecules to Nile Red molecules in Langmuir-Blodgett films are presented. The observed sensitized delayed fluorescence of the energy acceptor is shown to be due to annihilation of migrating triplet excitons. It has been found that the decay kinetics of delayed fluorescence of the donor and the acceptor has a complex form and is described by a combination of the power and exponential functions. The dependence of the energy transfer efficiency on the distance between the donor and acceptor layers was studied.